(untitled) (Third Sector Social Economic Review, 2023)
Increasing requirements for corporate transparency have encouraged firms to report information about economic, social, environmental performance to shareholders, investors, and stakeholders generally. However, many corporate reports present challenges during the analysis phase. Integrated reports have emerged to help minimize this problem. These reports address various non-financial data such as the firm’s risk management, social and environmental initiatives, corporate structure. Briefly, they contain comprehensive and integrated information about the firm’s activities. Thus, it helps to evaluate performance more realistic. The aim is to examine the impact of disclosing integrated reports on the cost of equity and financial performance (return on equity) of banks listed in Borsa Istanbul (BIST). It examines banks listed in BIST Banking Index over a period of seven years (2015-2021). Multiple regression model was used to analyze the impact of banks’ integrated reports on the cost of equity and return on equity. The empirical results obtained after applying panel data methodology reveal no significant relationship between disclosing integrated report, banks’ cost of equity and return on equity. This study makes a significant contribution to the academic literature by adding to the limited research on the impact of disclosing integrated report on the cost of equity and financial performance.